Social Networking in Improving School Promotion Based on SWOT Analysis - Nareswari Tiara DS; Bambang Ismanto (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2024)
After COVID-19, all educational institutions began to innovate in promoting schools, especially in accepting new students. Perwari Kendal Vocational School is starting to optimize networking media as a marketing tool for accepting new students. This research aims to evaluate Perwari Kendal Vocational School's strategy to optimize networking media as a means of marketing new student admissions. This research is a qualitative descriptive study with data triangulation by conducting interviews with the principal, deputy principal for student affairs, head of new student admissions, and students from the Catering and Beauty Services department. Using SWOT analysis as validation for optimizing the use of networking for marketing. The research results show that Perwari Kendal Vocational School has optimized the use of networking media as a marketing medium for accepting new students. This is strengthened by the collaboration between teachers and students in creating TikTok content and introducing various activities in the Catering and Beauty Services department. This marketing also makes it easier for the public to find information related to Perwari Kendal Vocational School. This research hopes that Perwari Kendal Vocational School will be more consistent in using networking media as a marketing tool in the Kendal Regency community.